Strengthening the World Bank - Reid, Escott (Chicago : Adlai Stevenson Institute, 1973)
This book is an attempt to look at the Bank Group as a whole. It was written from only by someone who knows from the inside how government operate, how difficult it is for them to choose between alternative policies, and who has participated in the making of big decisions on government policy.
Includes bibliographical references and index.
osa; 27/11/2018
Loans
Keywords: World Bank; Government policy